Linking litter decomposition of above- and below-ground organs to plant-soil feedbacks worldwide - Freschet, Grégoire T.; Cornwell, William K.; Wardle, David A.; Elumeeva, Tatyana G.; Liu, Wendan; Jackson, Benjamin G.; Onipchenko, Vladimir G.; Soudzilovskaia, Nadejda A.; Tao, Jianping; Cornelissen, Johannes H.C. (The Journal of ecology, 2013)
1. Conceptual frameworks relating plant traits to ecosystem processes such as organic matter dynamics are progressively moving from a leaf-centred to a whole-plant perspective. Through the use of meta-analysis and global literature data, we quantified the relative roles of litters from above-and below-ground plant organs in ecosystem labile organic matter dynamics. 2. We found that decomposition rates of leaves, fine roots and fine stems were coordinated across species worldwide although less strongly within ecosystems. We also show that fine roots and stems had lower decomposition rates relative to leaves, with large differences between woody and herbaceous species. Further, we estimated that on average below-ground litter represents approximately 33 and 48% of annual litter inputs in grasslands and forests, respectively. 3. These results suggest a major role for below-ground litter as a driver of ecosystem organic matter dynamics. We also suggest that, given that fine stem and fine root litters decompose approximately 1.5 and 2.8 times slower, respectively, than leaf litter derived from the same species, cycling of labile organic matter is likely to be much slower than predicted by data from leaf litter decomposition only. 4. Synthesis. Our results provide evidence that within ecosystems, the relative inputs of above-versus belowground litter strongly control the overall quality of the litter entering the decomposition system. This in turn determines soil labile organic matter dynamics and associated nutrient release in the ecosystem, which potentially feeds back to the mineral nutrition of plants and therefore plant trait values and plant community composition.